Effect of Action and Active Compounds of Leaf Vocational Leaf (Tristania Whitiana Griff.) on Bacteria Shigella Dysenteriae - Purnamasari, Septi; Joko Marwoto (Experimental Student Experiences, 2023)
The purpose of this study was to determine the ability of the antibacterial activity of pelawan leaf fractions and active compounds against Shigella dysenteriae bacteria. This research includes in vitro laboratory experimental research. The subject of this research is the bacterium Shigella dysenteriae. The results showed that the MIC value of the n-hexane fraction against Shigella dysenteriae was 125 mg/ml and the MIC value of the active compound n-hexane fraction was 62.5 mg/ml. Determination of the class of active compounds from the purification of the n-hexane fraction of Pelawan leaves obtained flavonoid compounds. The concentration equivalence test showed that 1 mg/ml n-hexane fraction was equivalent to 0.004 mg/ml ampicillin against Shigella dysenteriae bacteria and 1 mg/ml active compound flavonoid was equivalent to 0.01 mg/ml ampicillin against Shigella dysenteriae bacteria. It can be concluded that the active fraction of n-hexane and its compounds have positive antibacterial effectiveness against Shigella dysenteriae bacteria.